2018
DOI: 10.1021/acs.inorgchem.7b03238
|View full text |Cite
|
Sign up to set email alerts
|

Coordination Chemistry of a Strongly-Donating Hydroxylamine with Early Actinides: An Investigation of Redox Properties and Electronic Structure

Abstract: Separations of f-block elements are a critical aspect of nuclear waste processing. Redox-based separations offer promise, but challenges remain in stabilizing and differentiating actinides in high oxidation states. The investigation of new ligand types that provide thermodynamic stabilization to high-valent actinides is essential for expanding their fundamental chemistry and to elaborate new separation techniques and storage methods. We report herein the preparation and characterization of Th and U complexes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 83 publications
2
34
0
Order By: Relevance
“…[14][15] However, the [2-( t BuNO)py]hydroxylaminato ligand was recently shown to provide a -1.82 V stabilization of the +4 oxidation state of cerium, versus Fc/Fc + in THF. 16,17 It was also reported that [2-( t BuNO)py]could stabilize the +5 oxidation state of uranium as evidenced from electrochemical studies that demonstrated a one-electron oxidation of a U(IV)hydroxylaminato complex to form a U(V) complex. 17 Expanding understanding of the redox chemistry of hydroxylaminato/nitroxide ligands (and those with related bonding and electronic properties) to transuranium elements enhances fundamental understanding of f-element bonding and redox properties and may afford development of new classes of separations agents.…”
Section: Introductionmentioning
confidence: 96%
“…[14][15] However, the [2-( t BuNO)py]hydroxylaminato ligand was recently shown to provide a -1.82 V stabilization of the +4 oxidation state of cerium, versus Fc/Fc + in THF. 16,17 It was also reported that [2-( t BuNO)py]could stabilize the +5 oxidation state of uranium as evidenced from electrochemical studies that demonstrated a one-electron oxidation of a U(IV)hydroxylaminato complex to form a U(V) complex. 17 Expanding understanding of the redox chemistry of hydroxylaminato/nitroxide ligands (and those with related bonding and electronic properties) to transuranium elements enhances fundamental understanding of f-element bonding and redox properties and may afford development of new classes of separations agents.…”
Section: Introductionmentioning
confidence: 96%
“…The Schelter group has reported the synthetic chemistry for a series of pyridyl-hydroxylamines ( R pyNOH) and demonstrated their redox activities [10]. Metal complexes of these ligands have been prepared for several f-block [11][12][13][14][15] and transition [16][17][18] metals. Inspired by these compounds we prepared and fully characterized aluminum complexes of the type ( R pyNO − ) 2 AlCl ( R pyNO − = N-tert-butyl-N-(2-(5-R-pyridyl))nitroxyl, R = H, CH 3 , CF 3 ) [7] and {(µ-R pyNO − )Al(CH 3 ) 2 } 2 (R = H, CH 3 ) [8] and explored their electrochemical behavior.…”
Section: Introductionmentioning
confidence: 99%
“…This is mainly due to the potential of Th for the next generation of nuclear fuel, as the development of liquid-fluoride thorium reactors is close to commercialization [40,71]. Since the main Th production mineral is monazite, which also contains Ln III ions, there is an urgent need for the discovery of suitable organic ligands and efficient solid adsorbents for the selective extraction of Th 4+ from 4f-metal ions [72,73]. Other research topics of interest in the Th(IV) complexes field are studying the solutions and solid products arising from Th(IV) hydrolysis [35]; the investigation of Th(IV)-peroxide chemistry [74]; the incorporation of this diamagnetic metal ion into isostructural heterometallic d/U IV clusters with the goal of elucidating the d-d magnetic exchange interactions [75]; the structural characterization of complexes with very high coordination numbers and novel polyhedra [41]; the progress in complexes with Th(IV)-ligand multiple bonds [76,77]; the stabilization of novel secondary building units in Th(IV) metal-organic frameworks [78]; the study of the electronic and thermodynamic properties of Th(IV)/An(Z) (Z = various oxidation states) and An(Z)/Th(IV)/3d-metal ion MOFs (Metal-Organic Frameworks) with "structural memory" [79]; and the in-depth investigation of Th(IV) interactions with ionic liquids to model aspects of the An ions extraction from radioactive feeds [42].…”
Section: Dinuclear and Oligonuclear Thorium(iv)-schiff Base Complexesmentioning
confidence: 99%